Impact of Macro Economic Variables on Stock Price Movements with Special Reference to BRIC Countries: An Empirical Review - Tamilselvan , B.; Karthigeyan , Dr.K.T. Vijay (International Journal of Accounting and Economics Studies, 2025)
Market forces that have an impact on the economy are generally known as macroeconomic factors.  Any number of external influences, some of which are natural and others of which are man-made, may alter the trajectory of an economy.   Natural catastrophes such as earthquakes, famines, and droughts, as well as man-made events such as war, worldwide inflation, recession, and so on, are examples of such macroeconomic forces.  The rate of increase of gross domestic product (GDP), stock market movements, important industries, and other fundamental economic indicators are all affected by these variables.  As a result, knowing these elements and how they affect the economy overall is crucial. These macroeconomic variables influence stock markets by affecting corporate profitability, investor sentiment, and the overall economic outlook. Strong macroeconomic indicators can lead to a bullish market sentiment, while weak indicators can result in bearish sentiment. The relationship between stock prices and the global economy may not stay the same and can shift in line with various economic and market conditions. The present work is a descriptive review of the empirical evidences and presents the findings to establish the need for the research during post post-COVID-19 period. The reason behind, the post-pandemic period selection is the preferences, patterns, and practices of many corporates about investments have changed and thereby macroeconomic factor dynamics are also varied. In this parlance, the research can help to undergo a review of the situation and make policy changes to bring sustainability and growth into the mainstream of an economy. Hence, the paper's principal goal is to establish the need for research and identify the research gap in the area. The findings of the current paper reflects that the macroeconomic factors and stock price have a substantial correlation. movements with special reference to BRIC countries during the past decade and continue to be dynamic with corrections, suggest the role of regulatory and governments to be vigilant and dynamic in taking policy decisions from time to time based on the macroeconomic key variables, which can help to maintain the perpetual growth and sustainability of economies.
Keywords: Volatility; Market Structures; Inflation; Regulation; Market Trends